(untitled) - Kamien, Roger (Boston, Mass., 2002)
When it comes to writing a text for non-music majors, Kamien knows the score. With the care you would expect from the concert pianist he is, Kamien introduces the musical elements and repertoire thoroughly and clearly, without assumptions of prior knowledge but also without condescension. As a teacher at Queens (NY) College, Kamien developed the concept of the Listening Outline, which he incorporated into the first edition of Music: An Appreciation and which he has refined and enhanced in every subsequent edition. This is a text with which students of all levels and backgrounds can feel comfortable.
Keywords: Music appreciation,Đánh giá âm nhạc